A tale of two countries: Cash demand in Canada and Sweden - Walter Engert; Ben Fung; Björn Segendorff (Sveriges Riksbank, 2019)
Cash is being used less and less for making payments in many countries, including Canada and Sweden, which might suggest that cash will eventually disappear. However, cash in circulation in most countries, including Canada, has been stable for decades, and even rising in recent years. In contrast, aggregate cash demand in Sweden has been falling steadily. This paper explains these differences between Canada and Sweden by focusing separately on the transactions demand for cash and on the store-of-value demand. We find a long-term downward trend in small-denomination bank notes relative to gross domestic product in both Canada and Sweden. This reflects similar experiences in decreasing cash use for transactions over time due to the adoption of payment innovations. This means that payment innovations and diffusion are not sufficient to explain why aggregate cash demand has been declining rapidly in Sweden but not in Canada. Instead, the difference in the trends of cash demand between these two countries is due more to the behaviour of larger-denomination, store-of-value bank notes. Finally, we identify influences and frictions that help explain the persistent decline in the demand for larger bank notes in Sweden relative to Canada.
Keywords: E; E4; E41; E42; E5; 330; Bank topics; Bank notes; Digital currencies and fintech; Financial services; Payment clearing and settlement systems